CMT350 - Process Instrumentation / Faculty of Applied Sciences - UiTM, Faculty of Applied Science (Universiti Teknologi MARA (UiTM), 2023)
This is an introductory course involving theoretical and practical usage of process control systems, which gives students an insight into the historical background and the basic theoretical knowledge of the subject and the latest concept of Proportional, Integral, Derivative (PID) control modes. This course also exposes students to the various types of industrial controllers and related hardware available in industries and gives students the opportunity to learn ‘hands on’ about controller tuning.